Psychometric validation of Utrecht Work Engagement Scale-Student-9 in Chinese undergraduate students - Wei, Zhixia; Yang, Tiantian; Gu, Xiaoxia; Dong, Jingyi; Che Hassan, Norlizah (Frontiers Media SA, 2025)
Introduction: Academic engagement represents a critical construct in educational psychology, yet comprehensive psychometric validation of assessment instruments remains limited within Chinese higher education contexts. This study examines the psychometric properties of the Chinese version of the Utrecht Work Engagement Scale-Student-9 (UWES-S-9) among undergraduate students. Methods: Participants comprised 498 Chinese undergraduate students (66.1% female; Mage = 19.15 years, SD = 1.03, range: 17–24) who completed the UWES-S-9. A comprehensive analytical approach was employed, including confirmatory factor analysis (CFA), exploratory structural equation modeling (ESEM), and bifactor modeling (CFA and ESEM), alongside assessments of internal consistency, test-retest reliability, construct and concurrent validity, and measurement invariance across gender, academic year, and major. Results: The three-factor ESEM model demonstrated superior fit indices (χ2/df = 2.899, RMSEA = 0.062, CFI = 0.990, TLI = 0.971) compared to traditional CFA approaches. Bifactor analysis indicated that academic engagement is primarily characterized by a general factor accounting for 79% of common variance. The omega hierarchical coefficient for the general factor (ωH = 0.827) supported reliable interpretation of total engagement scores, while specific factor reliabilities were negligible (ωHS ≤ 0.149), suggesting limited utility of subscale scores. Measurement invariance testing supported configural, metric, and scalar invariance across gender, major, and academic year. Discussion: These findings contribute to the validation of the UWES-S-9 within Chinese higher education contexts while providing evidence for predominantly unidimensional interpretation of academic engagement scores. The results suggest that total engagement scores provide more reliable assessment than individual subscale scores, with important implications for both research and practical applications in Chinese educational settings.